A phase 2, randomized, double‐blind, placebo‐controlled study of siltuximab (anti‐IL‐6 mAb) and bortezomib versus bortezomib alone in patients with relapsed or refractory multiple myeloma. Issue 1 (January 2015) - Orlowski, Robert Z.; Gercheva, Liana; Williams, Cathy; Sutherland, Heather; Robak, Tadeusz; Masszi, Tamás; Goranova‐Marinova, Vesselina; Dimopoulos, Meletios A.; Cavenagh, James D.; Špička, Ivan; Maiolino, Angelo; Suvorov, Alexander; et al.
<x xml:space="preserve">Abstract</x> We compared the safety and efficacy of siltuximab (S), an anti‐interleukin‐6 chimeric monoclonal antibody, plus bortezomib (B) with placebo (plc) + B in patients with relapsed/refractory multiple myeloma in a randomized phase 2 study. Siltuximab was given by 6 mg/kg IV every 2 weeks. On progression, B was discontinued and high‐dose dexamethasone could be added to S/plc. Response and progression‐free survival (PFS) were analyzed pre‐dexamethasone by European Group for Blood and Marrow Transplantation (EBMT) criteria. For the 281 randomized patients, median PFS for S + B and plc + B was 8.0 and 7.6 months (HR 0.869, P = 0.345), overall response rate was 55 versus 47% (P = 0.213), complete response rate was 11 versus 7%, and median overall survival (OS) was 30.8 versus 36.8 months (HR 1.353, P = 0.103). Sustained suppression of C‐reactive protein, a marker reflective of inhibition of interleukin‐6 activity, was seen with S + B. Siltuximab did not affect B pharmacokinetics. Siltuximab/placebo discontinuation (75 versus 66%), grade ≥3 neutropenia (49 versus 29%), thrombocytopenia (48 versus 34%), and all‐grade infections (62 versus 49%) occurred more frequently with S + B. The addition of siltuximab to bortezomib did not appear to improve PFS or OS despite a numerical increase in response rate in patients with relapsed or refractory multiple myeloma. © 2014 Wiley Periodicals, Inc. Am. J. Hematol. 90:42–49, 2015. © 2014 Wiley Periodicals, Inc.